2003
DOI: 10.1046/j.1439-0418.2003.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of repellent ingredients from Lantana camara (Verbenaceae) flowers and their repellency against Aedes mosquitoes

Abstract: The repellent properties of different fractions isolated from Lantana camara flowers by using steam distillation, solvent partition and chromatographic methods were evaluated against Aedes mosquitoes. Maximum protection time of one fraction eluted by chloroform from a silica gel column was 3.45 h. One application of this fraction gave 100% protection for 2 h and may protect 75.8% at 7 h (t ¼ 7.00, P < 0.001) against the bites of Aedes mosquitoes. Further purification of the most efficient fraction into pure co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 3 publications
0
51
1
3
Order By: Relevance
“…vittatus and Ae. aegypti) (Dua et al, 2003). The results showed that one application of the chloroform fraction gave 100% protection for 2 h and up to 75.8% protection at 7 h against Ae.…”
Section: Insecticidal Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…vittatus and Ae. aegypti) (Dua et al, 2003). The results showed that one application of the chloroform fraction gave 100% protection for 2 h and up to 75.8% protection at 7 h against Ae.…”
Section: Insecticidal Activitymentioning
confidence: 98%
“…They also have anti-rheumatic, stimulant and sudorific properties, and are used to treat bronchopulmonary disorders, and some species are utilized in biological control as a pesticide (Ghisalbert, 2000;Dua et al, 2003;. Organic extracts and essential oils of Lantana have shown a wide variety of biological and pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Se sabe que Lantana camara posee actividad contra plagas que atacan granos almacenados, plagas de cultivos vegetales, mosquitos y larvas, así como también presentan actividad antifúngica y repelente (Sharma et al, 1988;Dua, Pandey, Singh, Sharma, & Subbarao, 2003). En el presente estudio se evaluó el aceite esencial extraído de hojas de Lantana camara sobre poblaciones Revista semestral de la DIUC 27 https://doi.org/10.18537/mskn.09.01.03 adultas de Drosophila melanogaster pertenecientes a la ciudad de Cuenca, Azuay, bajo condiciones de laboratorio.…”
Section: Resultados Y Discusiónunclassified
“…Water is transported into the core by permeation and hydrostatic pressure will be built up in the core and subsequently, the dissolved active agent comes out (Fan & Singh, 1989). In the field of controlled delivery, several newer techniques and methods like targeted delivery, viable cell immobilization, microspheres and nanoparticles/nanocomposites are finding great research interest (Hwang et al, 1985;Dua et al, 1996).…”
Section: Osmosis Controlled Systemmentioning
confidence: 99%